Energy status: Malaysia vs world - Islam, Syed Zahurul; Kamarudin, Muhammad Saufi; Tanvir, Faysal Amin; Abdullah, Mohd Noor
The whole world is now concerned about the energy as the continuous demand has great growth [1]. Across the globe, researches are being done and investments also have been increased to this regard to discover new sources for energy as well as to improve the efficiency of the existing systems. There are several number of energy scenarios suggested by several organizations such as the International Energy Agency (IEA), the United States Energy Information Administration (US EIA), World Energy Association (WEA), Renewable Energy Policy Network for the 21st Century (REN21), International Energy Agency (IEA), Nuclear Energy Institute and Energy Commission, Malaysia [2-4]. All scenarios depict energy generation capacity, consumption and foresee future demand by 2050. Based on different surveys and analyses suggested by these organizations, countries all over the world are following some trends and agenda items that are relevant to new energy and energy-related developments in regionally diverse systems. Renewable energy sources are the focus of the energy world in this matter. The visualizations shown here are the global production of renewable energy over the long-term. The generation and capacity of the whole world have been discussed by different fuels. Moreover, comparative, and analytical data of several countries regarded to energy are provided.